Bisphenol C induces developmental defects in liver and intestine through mTOR signaling in zebrafish (Danio rerio). (May 2023) - Liu, Jinfeng; Lin, Jiebo; Chen, Jiafeng; Maimaitiyiming, Yasen; Su, Kunhui; Sun, Siqi; Zhan, Guankai; Hsu, Chih-Hung
Abstract: Bisphenol A (BPA) was widely used in the plastic products and banned in infant food containers in many countries due to the environmental and biological toxicity. As a common substitute of BPA to manufacture products, Bisphenol C (BPC) is frequently detected in human samples like infants and toddlers' urine, indicating infants and young children are at risk of BPC exposure. However, the understanding of effects of BPC exposure on early development is limited. Herein, we evaluated the early developmental toxicity of BPC and studied the underlying mechanism in a zebrafish model. We found BPC exposure leading to liver and intestinal developmental defects in zebrafish, which occurred via disruption of GPER-AKT-mTOR-RPS6 pathway. Specifically, BPC downregulated phosphorylated and total levels of mTOR, which synergistically reduced the phosphorylation of RPS6, suppressing the translation of genes essential for cell proliferation in liver and intestine such as yap1 and tcf4 . Collectively, our results not only observed clear toxicity of BPC during liver and intestinal development but also demonstrated the underlying mechanism of BPC-mediated defects via disrupting the GPER-AKT-mTOR-RPS6 pathway. Graphical abstract: Image 1 Highlights: Bisphenol C causes liver and intestinal developmental defects in zebrafish. Bisphenol C downregulates phosphorylated and total levels of mTOR. Bisphenol C impacts the translation and cell proliferation in liver and intestine.